Functional lung rejuvenation in obese patients after bariatric surgery - Melo,Saulo Maia Davila (2016)
Summary Objective: To determine the lung age (LA) in obese people before and after bariatric surgery, compare the LA with the chronological age (CA) before and after the peration, and verify whether there was a functional pulmonary rejuvenation after it. Methods: A prospective longitudinal study including 43 morbidly obese patients who underwent bariatric surgery. The patients underwent clinical and spirometric evaluation in two stages, before and after the surgery. In both stages, LA, CA and spirometric variables were measured. Results: A significant improvement in the spirometric variables (FVC; FEV1; and FEV1/FVC ratio) was found after the operation (p≤ 0.0001). Comparing the LA before (50.93±13.36 years) and after the surgery (39.02±12.95 years), there was an important reduction of 11.90±9.12 years (95CI:9.10-14.71; p≤0.0001) in LA after surgery. The difference between LA and CA before surgery was 12.20± 11.71 years (95CI:8.60-15.81) with significant difference (p≤0.0001), and the difference between LA and CA after surgery was -1.95±11.83 years (95CI: -5.59-1.69) with no significant difference (p≤0.28). Regarding LA, we observed a pulmonary aging of 12.20±11.71 years before the surgery and a pulmonary rejuvenation of 11.90±9.12 years after it. Conclusion: Morbid obesity is responsible for early damage and functional accelerated pulmonary aging. After the correction of the body weight by surgery, there is a functional pulmonary rejuvenation demonstrated by the normalization of LA in relation to CA.